Direct measurements and modeling of congener group specific vapor pressure for chlorinated paraffins. (October 2021) - Hammer, Jort; Matsukami, Hidenori; Kuramochi, Hidetoshi; Endo, Satoshi
Abstract: Chlorinated Paraffins (CPs) are a complex group of manmade chemicals detected widely in the environment. To predict their environmental fate and effects, it is important to understand their physical-chemical properties including vapor pressure. In this study, the first direct measurements of the vapor pressure for CP congener groups (C10 – 16 Cl4–11 ) are presented. Vapor pressure was measured above three industrial CP mixtures with different congener distributions between 20 and 50 °C using a gas saturation method. The measured saturated vapor pressure ( P ∗ ) decreased with increasing carbon chain length and Cl content. Δ H vap ranged between 73 and 122 kJ mol −1, consistent with data from the literature and model prediction. The experimental log P ∗ at 25 °C agreed well with predictions from an empirical regression model in the literature ( R 2  = 0.97; RSME = 0.25) and with those predicted from the COSMO-RS-trained fragment contribution model ( R 2  = 0.95; RSME = 0.35). A new empirical model was calibrated with the P ∗ data for 35 congener groups measured in this study. Predicted log P ∗ values correlate well with field-measured gas/particle partition coefficients and may therefore be used for estimating the environmental fate and pathways of a broad range of CPs in the environment. Graphical abstract: Vapor pressures of chlorinated paraffin congener groups were directly measured using a gas saturation method. The new data were used to develop a regression model and to evaluate existing prediction methods including a COSMO-RS-trained fragment contribution model. Image 1 Highlights: The first direct measurements of vapor pressures of CP congeners are presented. Vapor pressure of CPs is comparable to that of PCBs. The newly developed models can accurately predict vapor pressures of CPs.